Barriers and motivations to volunteers' participation in preventive vaccine trials: a systematic review. (4th May 2017) - Detoc, M.; Gagneux-Brunon, A.; Lucht, F.; Botelho-Nevers, E.
ABSTRACT: Introduction : The recruitment of volunteers in preventive vaccine trials (PVT) is a challenge, since vaccine hesitancy and debates on vaccines are combined to usual difficulties of enrollment in clinical trials. Areas covered : Current knowledge of the reasons leading to the volunteers' participation or non-participation in PVT mainly focuses on data from preventive HIV vaccine trials. A systematic PubMed search was conducted using PRISMA guidelines to identify articles or reviews that reported barriers and motivations to participation in PVT regardless of the targeted disease or population. Expert commentary : In view of the barriers and motivations reviewed here, improvements in recruitment could be made through a better explanation of the prevented disease, of the expected individual and collective benefit and of all ethical protective principles associated to the trials. Use of decision aids as well as patient and public involvement may improve given information and may enhance comprehension of participants and their participation in PVT. Further prospective and interventional studies are needed to analyze if these leads may improve acceptation level in PVT.